(untitled) (Revista de Ciências Agroveterinárias, 2025)
The objective of this study was to evaluate the emergence of Fabaceae seedlings: butterfly-pea, puero and Campo Grande stylosanthes in goats and sheep feces in order to check if the stools allow the initial development of these plants; and the effects of the passage through digestive tract. For this, 50 g of each Fabaceae seed were offered mixed with concentrated to nine sheep and nine goats, both with mean body weight of 40 kg. Animal feces were collected at six hours intervals up to 72 hours after the ingestion of the seeds, and taken immediately to the greenhouse after each collection. It was evaluated the total number of seedlings emerged in the feces and the emergence rate index (GSI) for thirty days after ingestion of the seeds. It was used a completely randomized design in a factorial scheme: 3 Fabaceae x 12 collection times, with three replicates (animals). The best performance for total number of seedlings germinated in goats and sheep feces was obtained by puero, followed by stylosanthes. Butterfly-pea presented poor results due to high degradation of seeds by mastication. Goats and sheep feces do not prevent seedling emergence for the species assessed, so these animals can be considered true seed dispersers of these plants in pastures.